Culturas anuais e de cobertura na safrinha em sucessão à soja em plantio direto : fitomassa, ciclagem de nutrientes e produtividade de grãos - Greco, Tássia Maira (2020)
Brazil is the second largest producer of soybeans in the world, with 116 million tons, with the increase in demand, the increase in productivity becomes fundamental. The no-tillage system (SPD) is an alternative to the sustainability of agricultural production, as it promotes greater efficiency in the soil-plant-atmosphere system, favors soil fertility and the development of crops. The practice of crop rotation is the main obstacle to SPD, due to the predominance of cultivation in succession of crops with soy in the summer and corn in the off-season. In this way, the objective of the work was to identify alternatives for annual crops and cover for succession of soybeans, therefore, the study evaluated the production and decomposition of phytomass, nutrient cycling and increase in crop productivity in succession. The experiment was conducted at the Federal University of Mato Grosso – UFMT, University Campus of Rondonópolis, in the 2014/2015 to 2018/2019 seasons. The area's soil is classified as an Oxisol. The experiment was carried out in a randomized block design, with nine production systems, sown in safrinha, and with four replications each, totaling 36 experimental plots. Collections of phytomass and nutrient accumulation took place at 0, 15, 30, 60, 90 and 120 days after desiccation. Soybean productivity in succession was positively influenced by all treatments, except for fallows and S8. The systems intercropped with parallel corn have the largest accumulations of phytomass. A synchronization of nutrient release with the demand of the crop in succession reflected directly in the production results. Legume systems accumulate more nitrogen, while the use of sunflower increases the accumulation of potassium. Systems with U.ruziziensis were produced in the production of phytomass and in the cycling of nitrogen and phosphorus.